Towards Better Understanding of Molecular Solvent Behavior in Ionic Liquid-Biopolymer Mixtures. (30th August 2016) - Fox, Eric T; Fahey, Patrick J; Gobet, Mallory; Munoz, Stephen; Head, Audrey C.; Greenbaum, Steven; De Long, Hugh C; Trulove, Paul C
Abstract : The physical and transport properties (density, viscosity, ionic conductivity, and ion diffusion coefficients) are reported for solutions containing 1-ethyl-3-methylimidazolium acetate (EMIAc) and cellulose, either with no molecular solvent, with water, or with acetonitrile (AN). Ionicity values, or the fraction of ions present in the ionic liquid (IL) that are "free" were calculated for each solution. The addition of molecular solvents to IL-cellulose solutions significantly changes the association behavior of the ions, with the presence of acetonitrile increasing aggregation while water decreases aggregation. Adding cellulose to all solutions results in more ideal behavior from the IL, with the increase in ideality being a function of the type of solvent present. The observed behavior suggests that water and AN have fundamentally different interactions with EMIAc and these differences in interaction may explain the varying cellulose solvation behavior of solutions containing these solvents.